2007
DOI: 10.1002/anie.200604166
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Na+‐Templated Formation of [2]Pseudorotaxanes Exhibiting Significant Optical Outputs

Abstract: The diverse range of binding geometries exhibited by metal ions and their relatively stable interactions with ligands can be exploited for the efficient template-directed synthesis of macrocycles,[1] supramolecular architectures, [2] and interlocked molecules.[3] Although the formation of rotaxanes or pseudorotaxanes has been demonstrated using transitionmetal ions coordinated to four (tetrahedral and square planar), [4] five (trigonal bipyramidal and square pyramidal), [5] and six (octahedral) [6] donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…We later reported the alkali metal ion-templated formation of [2]­pseudorotaxanes from squaraine- and anthraquinone-based guests and a molecular cage as the host . The solid-state structures of these two types of [2]­pseudorotaxanes (Scheme ) revealed the chelation of the two CO oxygen atoms of the guest to the Na + ions, which were themselves complexed to the [18]­crown-6 (18C6) openings of the molecular cage.…”
Section: Inspiring Literature Precedentsmentioning
confidence: 99%
“…We later reported the alkali metal ion-templated formation of [2]­pseudorotaxanes from squaraine- and anthraquinone-based guests and a molecular cage as the host . The solid-state structures of these two types of [2]­pseudorotaxanes (Scheme ) revealed the chelation of the two CO oxygen atoms of the guest to the Na + ions, which were themselves complexed to the [18]­crown-6 (18C6) openings of the molecular cage.…”
Section: Inspiring Literature Precedentsmentioning
confidence: 99%
“…If either component of ammonium phosphate was chemisorbed onto the surface of the PMPS particles, then the particles, either before or after compounding into polymer fibres, would not consistently leach phosphate over numerous washing events. However, there is evidence, in two previously reported X-ray crystal structures, that squarate oxygen atoms are capable of co-ordination with metals (Hsueh et al., 2007a,b). Thus, direct metal co-ordination with the squarate oxygens in the PMPS pores must also be taken into account, which is suspected, in corporation with the specific pore sizes, to give rise to the differences in metal element uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Intuitively, use of the slippage approach 6 toward rotaxane synthesis would minimize the squaraine dye's contact with nucleophiles during the rotaxane formation process. Previously, we reported that Na + ions could be used to template the formation of a [2]pseudorotaxane from a squaraine dye and a molecular cage in CH 3 CN . Herein, we report high- yield slippage syntheses of corresponding [2]rotaxanes from this unique Na + ion-templated recognition system and the photophysical properties and enhanced chemical stability of the encircled squaraine dye.…”
mentioning
confidence: 92%